The faithfulness achieved by Julio Gomez de la Serna and Carmen Torres Pinillos in the translation of the tale the fall of the house of usher by Edgar Allan Poe with regards to text style, a stylistic feature and language register - Abrego de Escobar, Magaly del Carmen
This research project addressed the faithfulness in translation through the analysis of a very well-known tale called “The fall of the house of usher” written by Edgar Allan Poe many decades ago. The story is categorized as a gothic writing and contains very peculiar traits of the writer as for example the so called single effect. Two famous translators: Julio Gomez de la Serna and Carmen Pinillos translated this tale, others also did; yet, the ones selected for this inquire were the two of them. The main objective of this project has been to find out aspects of faithfulness in the translation of the mentioned story. The elements considered were the text style, the stylistic features and language register. The first specific goal was to identify the translators’ faithfulness to the stylistic features and this included the mood; the second goal was to determine the faithfulness to the text style, knowing that it is governed by the gothic romanticism. For that reason, the focus was the setting and the characters. The final specific goal was to identify the faithfulness to the language register, being this formal literary language. All these have been the guiding objectives of this study which intended to shed light into the importance of faithfulness for a high quality translation and to the impact it might have on the readers. In order to achieve the goals of this research, the methodology applied was content analysis. This type of method pertains to the study of documents and written materials. For this thesis, the units of analysis were words, phrases and statements. For this purpose, the two stories of the aforementioned translators: Julio Gomez de la Serna, and Carmen Pinillos were read and then classified in sections. The source story was also read and studied. After that, the researcher created different comparative charts that were filled with vocabulary, phrases and sentences. Then, they were compared with the source story and between the two versions, this process revealed very important data. The findings of this study have been surprising and unexpected. In short, it was found that both translators strove in their work. It iii is definitely not easy to follow Poe in his style, intention and literary experience. It is important to emphasize that from the two translators, Carmen Torres Pinillos was more faithful to the romanticism and Gothicism present in the story. Gomez de la Serna appears to be more practical in his elections and more superficial. Of course, this is not absolute; however according to the samples analyzed in this research that is the main conclusion coined from the author of this projec